Quranic Education for Deaf Students in Malaysia; Implementation and Challenges - Izuli Dzulkifli (Nadwa: Jurnal Pendidikan Islam, 2022)
Deaf students have the right to enjoy formal Quranic Education in schools. Teachers are supposed to plan and execute teaching plans that suit deaf students' abilities. This research aimed to explore the Quran teaching syllabus adopted by teachers and the challenges teachers faces at primary school deaf students in Selangor. This research took a qualitative approach in the case study that employed interview techniques and document analysis to obtain data. Five teachers from the Special Education Integration Program and one from Special Education Primary School were selected as respondents in the research. The selection was made considering their experience in teaching al-Quran to deaf students for at least five years. The interview outcome was strengthened by feedback given by other prominent interviewees, two officers of the Ministry of Education, and an analysis of relevant documents on the Quranic Education of deaf students. This research revealed that teachers used the teaching syllabus mandated by the Ministry of Education and modified the syllabus to suit students' disabilities using Bahasa Melayu Hand Code as a teaching medium. Teachers face challenges in teaching al-Quran to deaf students, such as a lack of teaching training and suitable teaching aids. This research contributed to suggestions on teaching training and innovative teaching aids that could assist teachers in imparting knowledge on al-Quran to deaf students.